2007
DOI: 10.1001/archpedi.161.5.507
|View full text |Cite
|
Sign up to set email alerts
|

Supine Sleeping Position Does Not Cause Clinical Aspiration in Neonates in Hospital Newborn Nurseries

Abstract: Objectives: To determine the frequency and severity of clinically significant events of spitting up in normal newborns during the first 24 hours of life and to correlate the events with sleeping position.Design: Prospective observational study. Participants: Healthy full-term newborns (n = 3240) (Ն37 weeks estimated gestational age) during the first 24 hours of life.Outcome Measures: Frequency of, and intervention required for, spitting up in supine, side-lying, and prone positions while asleep and awake.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…19,20,26 There are no data supporting an increased risk of aspiration while supine, and deaths attributable to aspiration have not increased since supine positioning was first recommended. [27][28][29] Additional efforts to understand and to address barriers to changes in attitudes and behaviors are important if continued progress in achieving safe sleep environments in child care settings is to be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…19,20,26 There are no data supporting an increased risk of aspiration while supine, and deaths attributable to aspiration have not increased since supine positioning was first recommended. [27][28][29] Additional efforts to understand and to address barriers to changes in attitudes and behaviors are important if continued progress in achieving safe sleep environments in child care settings is to be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that the risk of aspiration is not increased by sleeping in the supine position. [24][25][26] This is also true for infants with gastro-oesophageal reflux.…”
Section: Sleeping Positionmentioning
confidence: 94%
“…Multiple studies in different countries have not found an increased incidence of aspiration since the change to supine sleeping. [81][82][83] There is often particular concern for aspiration when the infant has been diagnosed with gastroesophageal reflux. The AAP supports the recommendations of the North American Society for Pediatric Gastroenterology and Nutrition, which state that infants with gastroesophageal reflux should be placed for sleep in the supine position, with the rare exception of infants for whom the risk of death from gastroesophageal reflux is greater than the risk of SIDS 84 -specifically, infants with upper airway disorders for whom airway protective mechanisms are impaired, which may include infants with anatomic abnormalities, such as type 3 or 4 laryngeal clefts, who have not undergone antireflux surgery.…”
Section: Figurementioning
confidence: 99%